Exploring the factors that influence the experience of joy in late adulthood: a qualitative study on South African Indian elderly adults, using in-depth interviews - Dadabhay, Shazia (The IIE, 2020)
This dissertation examines the joys of being an Indian South African individual in late adulthood, therefore allowing people to view the elderly in a more positive manner. By examining these joys, the researcher clarifies how middle-aged individuals can accept aging as a normal process that comes with its own joys and benefits, as well as how ageist stereotypes against older people are false. The researcher examines two theories in order to further aid her research. These theories include: the age-related positivity effect, as well as the theory of psychosocial development. The researcher also looks at previous research and identifies themes relating to the research such as, integrity versus despair, subjective wellbeing, social support in old age, and the effects of a positive outlook on wellbeing. The researcher uses an interpretivist paradigm. She uses a qualitative methodology and follows an inductive line of reasoning. Two non-probability sampling methods are used: (1) convenience sampling and (2) purposive sampling. Data has been collected from interviews and published reports. The population parameters of the study include individuals who are elderly, South African, and have an Indian ethnicity. Five themes were ascertained within the conducted interviews, which comprise of interpersonal relationships; religious and/or spiritual affiliation; hobbies and/or daily activities; appreciation of life; and a lack of regret in one’s life. This dissertation finds that interpersonal relationships among other factors, is one of the largest contributors to joy for Indian elderly South African’s.
Keywords: Experience of joy; Late adulthood; Indian; Elderly adults; South Africa